Postoperative apnea among premature or anemic infants undergoing inguinal hernia repair - Alireza Mahdavi; Leili Mohajerzadeh; Sajad Razavi; Mehdi Ghahremani; Hossein Moeini; Afsaneh Sadeghi; Parastou Ariana (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2017)
Introduction: Premature or anemic newborns undergoing hernia repair are prone to more postoperative complications than full-term infants. The incidence of respiratory complications among these patients is more than 30%, being postoperative apnea the most common. Some investigators found that gestational and postconceptional age, the presence of continuing apneic episodes and anemia are the main determinants of postoperative apnea. It seems that infants who do not receive intravenous anesthetics experience less respiratory complications. Intravenous anesthetics have hepatic metabolism for elimination and the immature liver of the premature has not sufficient elimination capacity.  Materials and Methods: Study participants were 1047 neonates with post conceptual age (PCA) lower than 60 weeks undergoing inguinal hernia operation. Sevoflurane gas mask was used for anesthesia induction and during deep anesthesia, caudal block was administered using 1cc/kg bupivacaine 2%. The neonates were managed with spontaneous breathing with Sevoflurane gas mask or endotracheal tube until the end of the operation.  Results: In the present study, 916 (87.5%) male and 131 (12.5%) female neonates were included. Mean gestational age and PCA were 36.62 ± 38.0 and 46.80 ± 45.60 weeks respectively. Postoperative apnea did not occur in any patient.  Conclusion: Many studies confirm our findings that inhaled sedative drugs without hepatic or renal metabolism are safe for sedation of premature or anemic infants.